Factors Associated with Mortality of Intensive Care Unit Patients with Acute Kidney Injury at Cipto Mangunkusumo National Central General Hospital - Aida Lydia; Ruth V Rebecca; Rudyanto Sedono; Arif Mansjoer (Acta Medica Indonesiana)
Background: the incidence of acute kidney injury (AKI) in intensive care units is associated with increased mortality, post AKI morbidity and high treatment costs. Research on factors related to mortality of AKI patients in intensive care units in Indonesia, especially Cipto Mangungkusumo General Hospital has never been done. This study aims to determine the prevalence of AKI, mortality rate of AKI patients, and the factors associated with increased mortality of AKI patients in intensive care units in ICU Cipto Mangunkusumo General Hospital. Methods: this is a retrospective cohort study of all patients diagnosed with AKI in the intensive care unit at Cipto Mangunkusumo General Hospital, January 2015 - December 2016. An analysis of bivariate relationships with multvariate with STATA Statistics 15.0 between age > 60 years, sepsis, use of ventilator, ventilator duration, dialysis, oligoanuria, and APACHE II scores at admission with mortality. Results: the prevalence of AKI patients in the intensive care unit was 12.25% (675 of 5511 subjects) and 220 subjects (32.59%) of the 675 analyzed subjects died in the intensive care unit. Factors related to increased mortality in multivariate analysis were sepsis (OR 6,174; IK95% 3,116-12,233), oligoanuria (OR 4,173; IK95% 2,104-8,274), use of ventilator (OR 3,085; IK95% 1,348-7,057), (scores APACHE II at admission) 1/2 [OR 1,597; IK95% 1.154-2.209], and the duration of the ventilator (OR 1.062; IK95% 1.012-1.114). Conclusion: the prevalence of AKI patients and their mortality rate in the intensive care unit of Cipto Mangunkusumo General Hospital obtained 12.25% and 32.59%. Sepsis, oligoanuria, ventilators (APACHE II score at admission) 1/2, and ventilator duration are factors that are significantly associated with increased mortality of AKI patients in intensive care units.